Etika Komunikasi Digital dalam Perspektif Al-Qur’an: Reinterpretasi Akhlak Nabawi terhadap Fenomena Degradasi Moral di Media Sosial - Alifya Bussaina Karim (Al-Qolamuna: Journal Komunikasi dan Penyiaran Islam, 2026)
This article discusses the ethics of digital communication in the perspective of the Qur'an as a reinterpretation of the Prophet's Morals in response to the phenomenon of moral degradation on social media. This paper departs from the fact that rapid developments in the field of technology and information have a positive impact both locally and internationally, but these rapid developments in addition to having a positive impact also have a negative impact in several ways. By carrying out observations on social media, it was found that there were four problems of moral degradation that occurred on social media. Namely the spread of hoax news, freedom of expression, verbal aggressiveness, and individualism. Then by searching the verses of the Qur'an, hadith books, tafsir books, and other sources, it was found that there are four principles of communication ethics found in the Qur'an and hadith. Namely tabayyun, maintaining views, maintaining speaking manners, and establishing friendship. Based on these four principles, four digital communication ethics are formulated that must be applied as a solution to the moral degradation that occurs on social media. The four digital ethics are digital fact checking, digital content filtering, virtual narrative ethics, and cyber humanity citizenship. Abstrak Artikel ini bertujan membahas tentang etika konumikasi digital dalam perspektif Al-Qur’an sebagai reinterpretasi Akhlak Nabawi merespon fenomena degradasi moral di media sosial. Tulisan ini berangkat dari fakta bahwa Perkembangan pesat dalam bidang teknologi dan informasi memberikan dampak positif baik lokal maupun internasional namun perkembangan pesat tersebut selain berdampak positif juga memberikan dampak negatif dalam beberapa hal. Dengan melaksanakan observasi di media sosial dihasilkan terdapat empat problematika degradasi moral yang terjadi di media sosial. Yaitu merebaknya berita hoaks, kebebasan berekspresi, agresivitas verbal, dan individualisme. Kemudian dengan melakukan penelusuran pada ayat Al-Qur’an, kitab-kitab hadis, kitab tafsir, dan sumber-sumber lainnya dihasilkan terdapat empat prinsip etika komunikasi yang terdapat pada Al-Qur’an dan hadis. Yaitu tabayyun, menjaga pandangan, menjaga adab berbicara, dan menjalin silaturrahmi. Berdasarkan empat prinsip tersebut kemudian dirumuskan empat etika komunikasi digital yang harus diterapkan sebagai Solusi atas degradasi moral yang terjadi di media sosial. Empat etika digital tersebut yaitu digital fact checking, digital content filtering, virtual narrative ethics, dan cyber humanity citizenship.